Provisional Security of Creditors in Cross-border Civil and Commercial Matters - Neža Pogorelčnik Vogrinc (LeXonomica, 2020)
Provisional measures can be of utmost importance to creditors especially in relationships with a cross-border element. The Regulation 1215/2012 is the legal source that provides rules regarding the jurisdiction to issue a provisional measure but also offers imperfect provisions regarding the recognition and enforcement of foreign provisional measures issued in other Member States of the European Union. Due to the inadequate regulation, CJEU case law has played an important role, but nevertheless the article finds and opens new questions that have not yet been answered.